Visual responses of visitors towards daylighting in museums: A case study of Malaysia - Ahmad, Noraini; Sheikh Ahmad, Sabarinah; Talib, Anuar; Rostam, Rostam Yaman (Universiti Putra Malaysia Press, 2017)
Daylighting in historic buildings is not easy to manage as natural light fluctuates. This study aims to evaluate visitors’ visual responses and opinions towards daylighting in four selected galleries in museums. Intensity of illumination and visitors feedback were obtained through fieldwork. Instruments employed were data logger management system and light sensors at test points on showcases and display panels. The questionnaire was on the respondents’ perception of daylight conditions at two different display panels (against window wall-AWW and opposite window wall-OWW). The illuminance assessment and evaluation indicated that the display placement affected daylight distribution pattern while the daylighting pattern affected the visitors’ viewing satisfaction. The study examines daylight distributions and the visitors’ visual perception and satisfaction in relation to the exhibits and interior configuration of the museums. The study found significant effect of exhibit condition and interior design parameters on indoor daylight performance and visual comfort. The results of this study contribute to the planning of appropriate lighting to minimise visual discomfort in museums.